The Influence Of Work Culture And Human Resource Development On Employee Performance In The Health Department Of Lampung Province - Yasir, Apriyan; Sodirin, Sodirin (Universitas Dehasen Bengkulu, 2025)
The fact that occurs is that the work culture within the Dinas Kesehatan Provinsi Lampung is not working well, as can be seen from the attitude of employees who are less aggressive in achieving organizational goals, reluctant to show their best performance in contributing to the agency. Other problems related to human resource development are still not optimal. This indicates that training activities are still minimal both in terms of the number of technical training and employee participation. Looking at and observing the problems of work culture and human resource development as described above, it is reasonable to suspect that the accumulation of these problems has contributed to weak employee performance. The aim of this research is to determine the influence of work culture and human resource development on employee performance. The hypothesis in this research is that there is an influence of work culture and human resource development, either partially or simultaneously, on employee performance. The sample in this study consisted of 54 employees. Data collection techniques include observation, documentation and questionnaires. The data analysis method uses a quantitative approach with the help of SPSS version 21.0 statistical tools including calculation of validity tests, reliability tests, simple and multiple linear regression tests, t tests, F tests and coefficient of determination tests. The results of hypothesis testing show that work culture partially has a positive influence on employee performance with a contribution of 56.2%. Human resource development has a positive influence on performance with a contribution of 50.4%. Simultaneous hypothesis testing shows that work culture and human resource development together have a positive influence on performance with a contribution of 62.3%, while the remaining 37.7% is a variation of other variables outside this research.